2022
DOI: 10.1289/ehp9676
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Modulation of Differential Alternative Splicing in HaCaT Human Keratinocyte Cell Line Chronically Exposed to Arsenic for up to 28 Wk

Abstract: Background: Chronic arsenic exposure via drinking water is associated with an increased risk of developing cancer and noncancer chronic diseases. Pre-mRNAs are often subject to alternative splicing, generating mRNA isoforms encoding functionally distinct protein isoforms. The resulting imbalance in isoform species can result in pathogenic changes in critical signaling pathways. Alternative splicing as a mechanism of arsenic-induced toxicity and carcinogenicity is understudied. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 132 publications
(279 reference statements)
0
5
0
Order By: Relevance
“…GO analysis suggested that “slicing, via spliceosome” was slightly activated due to SDS exposure. Earlier, it was shown that alternative splicing induction may contribute to the changing proteomic landscape as at carcinogenesis, for example, in HaCaT cells after arsenic exposure 33 . In contrast, several metabolic pathways, such as negative regulation of apoptotic process and epidermis development, were downregulated after treatment of HaCaT cells with SDS.…”
Section: Resultsmentioning
confidence: 99%
“…GO analysis suggested that “slicing, via spliceosome” was slightly activated due to SDS exposure. Earlier, it was shown that alternative splicing induction may contribute to the changing proteomic landscape as at carcinogenesis, for example, in HaCaT cells after arsenic exposure 33 . In contrast, several metabolic pathways, such as negative regulation of apoptotic process and epidermis development, were downregulated after treatment of HaCaT cells with SDS.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to algorithm limitations, sequencing technology also encounters obstacles in identifying AS events. Currently, most studies identify and quantify splicing isoforms starting from bulk short-read RNA-seq data ( Cieślik and Chinnaiyan, 2018 ; Ferragut Cardoso et al, 2022 ; Toffali et al, 2023 ). These studies typically map the short-read RNA sequences to a reference genome using software such as MISO ( Katz et al, 2010 ) or rMATS ( Shen et al, 2014 ), or assemble de novo using tools including StringTie ( Pertea et al, 2015 ) or Trinity ( Grabherr et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysis and immunoblotting were performed as previously described ( Ferragut Cardoso et al, 2022 ). Briefly, cells were lysed using lysis buffer (10 mM Tris – HCl pH 7.4, 1 mM Na 2 − EDTA, 0.1 % SDS, 1 mM Na-Vanadate, 1 mM PMSF and 1 X protease inhibitor cocktail (Complete, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%